2021
DOI: 10.3390/ijms22052353
|View full text |Cite
|
Sign up to set email alerts
|

ATF3-Induced Mammary Tumors Exhibit Molecular Features of Human Basal-Like Breast Cancer

Abstract: Basal-like breast cancer (BLBC) is an aggressive and deadly subtype of human breast cancer that is highly metastatic, displays stem-cell like features, and has limited treatment options. Therefore, developing and characterizing preclinical mouse models with tumors that resemble BLBC is important for human therapeutic development. ATF3 is a potent oncogene that is aberrantly expressed in most human breast cancers. In the BK5.ATF3 mouse model, overexpression of ATF3 in the basal epithelial cells of the mammary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…To extend these results, we next focused on the ATF3 gene, which is activated by inflammation, interacts with NF-κB and promotes the progression of TNBC and other types of cancer 39 41 . Activating TFs, such as ATF3, heterodimerize with JUN and are also capable of binding to DNA in the absence of JUN 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To extend these results, we next focused on the ATF3 gene, which is activated by inflammation, interacts with NF-κB and promotes the progression of TNBC and other types of cancer 39 41 . Activating TFs, such as ATF3, heterodimerize with JUN and are also capable of binding to DNA in the absence of JUN 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…AP-1 associates with NF-κB p65 and regulates the NF-κB transactivation function 37 , 39 41 . We found that, like MUC1-C and NF-κB, the AP-1 JUN, FOS and ATF3 proteins occupy the SET1A and WDR5 pELSs and that silencing MUC1-C decreases their occupancy (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study suggested that TGF-β1 could induce the expression of ATF3, and the induced ATF3 upregulated the expression of TGF-β1 in MCF-1OCA1a cells, thus forming a positive feedback loop for TGF-β signaling. Further, upregulated ATF3 was observed to be vital for TGF-β1 to increase the expression of its Epithelial-Mesenchymal Transition (EMT)-related genes, including snail, slug, and twist, hence increasing BC cell motility (Yin et al 2010;Ku et al 2020;Yan et al 2021). Cell proliferation (cyclin A1), invasion (matrix metalloproteinase 13; MMP13), and metastasis (Runx2) genes were found to be ATF3 target genes (Kwok et al 2009;Gokulnath et al 2017;Rohini et al 2019Rohini et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…5 Such transcription factors are prevalent in BC, and one example is activating transcription factor-3 (ATF3). 6,7 ATF3 is a stress-inducible gene belonging to the activating protein 1 family, whose expression is associated with multiple diseases ranging from cancer to cardiac hypertrophy. 8 ATF3 has been implicated in regulating oncogenic activities through various mechanisms that either promote or suppress cancer progression depending on the cellular environment and the signaling pathways involved.…”
Section: Introductionmentioning
confidence: 99%